2015
DOI: 10.3109/01443615.2015.1004528
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity of platelet glycoproteins Ia and IIIa is associated with in vitro fertilisation implantation failure

Abstract: Thrombophilic genetic factors have been shown to play an important role in implantation outcome after in vitro fertilisation (IVF). In this pilot study we investigated the frequencies of glycoprotein Ia (GpIa)-C807T and GpIIIa-PlA1/PlA2 polymorphisms in 60 nulligravidae women with a history of unexplained IVF implantation failures and compared them with 60 healthy fertile women. We found statistically significant associations between the GpIa-C807T and GpIIIa-PlA1/PlA2 polymorphisms and IVF implantation failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…There is accumulating evidence that recurrent miscarriages, as well as IVF-ET failures, share extensive common pathogenetic mechanisms. We have previously reported that genetic heterogeneity of platelet glycoproteins Ia and IIIa associated with platelet-derived thrombophilia is a risk factor for recurrent IVF-ET failures [ 23 ], and subsequently, this finding was also confirmed for spontaneous miscarriages [ 24 ]. Similarly, the associations of proinflammatory PECAM-1 (Leu125Val) and P-Selectin (Thr715Pro) gene polymorphisms with unexplained spontaneous miscarriages as well as IVF-ET failures have been reported [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 92%
“…There is accumulating evidence that recurrent miscarriages, as well as IVF-ET failures, share extensive common pathogenetic mechanisms. We have previously reported that genetic heterogeneity of platelet glycoproteins Ia and IIIa associated with platelet-derived thrombophilia is a risk factor for recurrent IVF-ET failures [ 23 ], and subsequently, this finding was also confirmed for spontaneous miscarriages [ 24 ]. Similarly, the associations of proinflammatory PECAM-1 (Leu125Val) and P-Selectin (Thr715Pro) gene polymorphisms with unexplained spontaneous miscarriages as well as IVF-ET failures have been reported [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 92%
“…In a recent pilot study of 60 strictly selected women with unexplained recurrent IVF-ET failures excluding all cases with other known risk factors, we reported an increased occurrence of carriers of the Gpllla-PIA2 allele, in comparison with a control group of 60 fertile women with no history of pregnancy or vascular complications, resulting in an odd ratio of 2.9 and a stronger association for the younger participants [10]. Furthermore, in a previous study in Bulgaria, Ivanov et al [8] also found a 2.6-fold increased risk during the comparison of 67 women with IVF-ET failures with 96 fertile controls [11].…”
mentioning
confidence: 75%
“…The Gpllla-PIA2 factor especially in synergy with the 807T allele of the glycoprotein la gene as we have shown recently [10] underlines the importance of the platelet-associated thrombophilia and could have a remarkable clinical impact on potential medical intervention with an individualized approach of the aspirin therapy to improve unexplained poor IVF implantation outcome [14].…”
mentioning
confidence: 91%
“…Furthermore, P-Selectin receptors participate in the interactions leading to Th1 lymphocyte migration into the decidua which is involved in the rejection of trophoblast cells [ 20 ]. It has been suggested that genetic alterations of platelet membrane factors, including PECAM-1 and P-Selectin, are synergistically involved in the pathogenesis of miscarriages [ 10 ] and implantation failure [ 9 , 21 , 22 ]. In a relative study, Dendana et al [ 23 ] found a statistically significant association between the presence of the G allele of another P-Selectin gene polymorphism (P-Selectin-C2123G, rs6127) and recurrent pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%